Association of Helicobacter pylori with colorectal cancer development. - Fouad Alsamaka, Fadi; Abdulamir, Ahmed Sahib; Khalid Mahdi, Laila; Alnaib, Khalid; Abu Bakar, Fatimah (IOS Press, 2010)
Background: Helicobacter pylori (H. pylori) may be associated with colorectal cancer. However, the underlying mechanisms are still unclear. Objectives: Explore the serostatus of H. pylori cytotoxicity-associated gene A product (CagA) in patients with colorectal carcinoma, and assess the association of H. pylori with colorectal cancer via c-Myc and MUC-2 proteins at tumor tissues. Methods: H. pylori CagA IgG antibodies were screened using enzyme-linked immunosorbent assay (ELISA) in 30 patients with colorectal carcinoma and 30 cancer-free control subjects. Paraffin-embedded blocks were examined for the expression of c-Myc and MUC-2 protein by immunohistochemistry. Results: H. pylori CagA seropositivity increased significantly among colorectal cancer patients (p <0.05). The expression of c-Myc and MUC-2 in colorectal carcinoma patients was over-expressed (80%), and downexpressed (63%) in resection margins (p <0.05). c-Myc over-expression and MUC-2 down-expression were associated with CagA-positive rather than CagA-negative H. pylori patients. In 16 CagA seropositive vs. 14 CagA seronegative patients, the expression rate was 97.3% vs. 64.2% and 33.3% vs. 78.5% for cMyc and MUC-2, respectively. CagA IgG level was significantly higher in positive than in negative c-Myc patients (p= 0.036), and in negative than in positive MUC-2 patients (p= 0.044). c-Myc and MUC-2 were positively and inversely correlated with CagA IgG level (p <0.05). Conclusions: CagA-seropositive H. pylori is most probably associated with colorectal cancer development. Part of the underlying mechanism for such association might be via alterations in expression of MUC-2, which depletes the mucous protective layer in the colo-rectum, and c-Myc, which stimulates the growth of cancerous cells.